Dynamic culture yields engineered myocardium with near-adult functional output. (December 2016) - Jackman, Christopher P.; Carlson, Aaron L.; Bursac, Nenad
Abstract: Engineered cardiac tissues hold promise for cell therapy and drug development, but exhibit inadequate function and maturity. In this study, we sought to significantly improve the function and maturation of rat and human engineered cardiac tissues. We developed dynamic, free-floating culture conditions for engineering "cardiobundles", 3-dimensional cylindrical tissues made from neonatal rat cardiomyocytes or human pluripotent stem cell-derived cardiomyocytes (hPSC-CMs) embedded in fibrin-based hydrogel. Compared to static culture, 2-week dynamic culture of neonatal rat cardiobundles significantly increased expression of sarcomeric proteins, cardiomyocyte size (∼2.1-fold), contractile force (∼3.5-fold), and conduction velocity of action potentials (∼1.4-fold). The average contractile force per cross-sectional area (59.7 mN/mm 2 ) and conduction velocity (52.5 cm/s) matched or approached those of adult rat myocardium, respectively. The inferior function of statically cultured cardiobundles was rescued by transfer to dynamic conditions, which was accompanied by an increase in mTORC1 activity and decline in AMPK phosphorylation and was blocked by rapamycin. Furthermore, dynamic culture effects did not stimulate ERK1/2 pathway and were insensitive to blockers of mechanosensitive channels, suggesting increased nutrient availability rather than mechanical stimulation as the upstream activator of mTORC1. Direct comparison with phenylephrine treatment confirmed that dynamic culture promoted physiological cardiomyocyte growth rather than pathological hypertrophy. Optimized dynamic culture conditions also augmented function of human cardiobundles made reproducibly from cardiomyocytes derived from multiple hPSC lines, resulting in significantly increased contraction force (∼2.5-fold) and conduction velocity (∼1.4-fold). The average specific force of 23.2 mN/mm 2 and conduction velocity of 25.8 cm/s approached the functional metrics of adult human myocardium. In conclusion, we have developed a versatile methodology for engineering cardiac tissues with a near-adult functional output without the need for exogenous electrical or mechanical stimulation, and have identified mTOR signaling as an important mechanism for advancing tissue maturation and function in vitro .